Decentralisation and Distribution: A Multi-Dimensional Taxonomy of Indonesian Districts - Dharendra Wardhana (Pusbindiklatren Bappenas, 2025)
Indonesia’s fiscal decentralisation devolves expenditure authority to districts, yet heavy reliance on central transfers and persistent spatial disparities indicate that a single, formula-based approach is ill-equipped to address heterogeneous needs. This study develops a multidimensional taxonomy of 403 districts, drawing on the World Bank’s INDO-DAPOER dataset and audit indicators, and applies hierarchical clustering. This study identifies four distinct clusters that differ systematically in structural transformation, human evelopment, local governance and autonomy. ANOVA confirms significant between-cluster differences, with population size, health and social protection expenditures exhibiting the strongest discriminating power. Policy-relevant profiles emerge: Cluster 1 concentrates poverty and weak governance yet depends most on transfers; Cluster 2 is agriculture-dependent with infrastructure emphasis; Cluster 3 is densely populated with strong human capital but limited fiscal capacity; Cluster 4 is economically advanced, least transfer-dependent but with room to improve governance. Findings inform targeted transfer design—combining performance-based incentives, differentiated sectoral allocations and capacity support—advancing decentralisation objectives by aligning resources to cluster-specific needs and strengthening accountability, local matching and service delivery.